Aspergillus baeticus sp. nov. and Aspergillus thesauricus sp. nov., two species in section Usti from Spanish caves - Nováková, Alena; Hubka, Vit; Saiz-Jimenez, Cesareo; Kolarik, Miroslav (International journal of systematic and evolutionary microbiology, 2012)
Two novel species of Aspergillus that are clearly distinct from all known species in section Usti were revealed during a study of microfungal communities in Spanish caves. The novel species identified in this study and additional species of Aspergillus section Usti are associated with places and substrates related to human activities in caves. Novel species are described using data from four loci (ITS, benA, caM and rpb2), morphology and basic chemical and physiological analyses. Members of the species Aspergillus thesauricus sp. nov. were isolated from various substrates, including decaying organic matter, cave air and cave sediment of the Cueva del Tesoro Cave (the Treasure cave); the species is represented by twelve isolates and is most closely related to the recently described Aspergillus germanicus. Members of the species Aspergillus baeticus sp. nov. were isolated from cave sediment in the Gruta de las Maravillas Cave (the Grotto of the Marvels); the species is represented by two isolates. An additional isolate was found in the Cueva del Tesoro Cave and in the Demänovská Peace Cave (Slovakia), suggesting a potentially wide distribution of this micro-organism. The species is related to Aspergillus ustus and Aspergillus pseudoustus. Both species were unable to grow at 37 °C, and a weakly positive, light greenish yellow Ehrlich reaction was observed in A. thesauricus. Unique morphological features alone are sufficient to distinguish both species from related taxa.
Keywords: Phylogeny; mykologické určovací techniky; Sequence Analysis, DNA; sekvenční analýza DNA; fylogeneze; jeskyně; Caves; DNA, Fungal; Spain; Španělsko; DNA fungální; Molecular Sequence Data; Mycological Typing Techniques; molekulární sekvence - údaje; Aspergillus